tg (5П/2+x) -3 tq ^2x=(cos2x-1) cos^-2…

Тема в разделе "Алгебра", создана пользователем Maximus1, 22 мар 2014.

  1. Maximus1

    Maximus1 Мелюзга

    Регистрация:
    8 дек 2013
    Сообщения:
    0
    Симпатии:
    0
    tg (5П/2+x) -3 tq ^2x=(cos2x-1) cos^-2 x
     
  2. Seren1ty

    Seren1ty Мелюзга

    Регистрация:
    5 ноя 2013
    Сообщения:
    0
    Симпатии:
    0
    Правильная записьtg (5pi/2+x) -3tgx^2=(cos2x-1)*cosx^ (-2) преобразуемtgx^2+1/tgx=0tgx^3=-1x=1/4 (4pi*n-pi) , n € Z
     

Поделиться этой страницей